Correction: Design, fabrication and anti-aging behavior of a multifunctional inorganic–organic hybrid stabilizer derived from co-intercalated layered double hydroxides for polypropylene. Issue 11 (3rd October 2019) - Zhang, Qian; Guo, Yixuan; Marek, Adam A.; Verney, Vincent; Leroux, Fabrice; Tang, Pinggui; Li, Dianqing; Feng, Yongjun
Abstract : Correction for 'Design, fabrication and anti-aging behavior of a multifunctional inorganic–organic hybrid stabilizer derived from co-intercalated layered double hydroxides for polypropylene' by Qian Zhang et al., Inorg. Chem. Front., 2019, 6, 2539–2549.